Procedural Justice in Continental & Anglo-Saxon Systems: Philosophical Comparative of Due Process & Rechtsstaat Principles - Agam Ibnu Asa Agam (Journal of Ius Comparatum Law Studies, 2025)
This study comparatively analyzes the philosophical nature of procedural justice in the Continental (Civil Law) and Anglo-Saxon (Common Law) legal systems, centered on the fundamental principles of Due Process of Law and Rechtsstaat. The debate over the balance of state authority and individual rights underscores the importance of this study, with foundations rooted in legal theory and political philosophy differing in both traditions. The purpose of this research is to identify similarities, differences, and potential convergence in ensuring justice in the legal process. The methodology used is an in-depth philosophical comparative analysis, tracing the philosophical foundations, historical evolution, and practical manifestations of the two concepts, beyond descriptive comparisons. The results show that despite coming from different historical and philosophical paths, the Anglo-Saxon (Due Process of Law) and Continental (Rechtsstaat) legal traditions show fundamental differences in approaches to procedural justice. Ontologically, Due Process is rooted in the empiricism and essence of ex-post individual protection through fair procedures, with epistemology growing out of case precedents. Meanwhile, ontologically, the Rechtsstaat is based on rationalism and the essence of a just and predictable state structure ex-ante through the codification of law, with epistemology derived from the systematization of coherent law. Despite these differences, the two legal traditions are increasingly facing similar challenges in the global legal landscape, indicating the potential for shared learning and reform. The novelty of this research lies in an integrated philosophical and comparative approach, uncovering the normative foundations of legal procedures and contributing to the understanding of the convergence of procedural justice in the global era.